Technologies For Creating Interactive Infographic Tools - Margubakhon Yunusaliyevna Eshnazarova; Ilkhomjon Kholmatjonugli Valijonov (Euro Asian Journal Publishing, 2023)
This article provides detailed information about Infographics and its types, principles, and technologies for creating infographics
Keywords: Infographics; statistics; information